Rancang Bangun Sistem Repositori Akreditasi Program Studi Ilmu Komputer di Universitas Negeri Jakarta - Kristanto, Aty Lestari; Indiyah, Fariani Hermin; Nurjanah, Siti (Universitas Negeri Jakarta, 2024)
This research aims to develop a document repository system for the accreditation of the computer science study program at Universitas Negeri Jakarta. The system is based on 9 criteria aligned with the Program Study Performance Sheet (LKPS), adhering to LAM INFOKOM regulations. This system is developed to facilitate data collection for accreditation, which is currently done manually. The development process follows the Agile Extreme Programming methodology. The system's final version will be tested using Black Box Testing to examine its features and components. The testing includes system functionality and usability assessments. The results indicated that the system's functionality scored 88.33%, and the usability testing scored 85.87%, demonstrating that the developed system is highly viable and meets the expected outcomes. Keywords: Accreditation, Agile, Extreme Programming, Black Box Testing